Problematika Membaca Teks Arab bagi Siswa Madrasah - Nur Khikmah (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2019)
Learning to read the text of the Qur'an and hadith at the initial level is to sound the letters of the Qur'an and the hadith itself. Learning to read the Qur'an means learning to pronounce written symbols (letters). The Qur'an and hadith are revealed in Arabic and become a foreign language in learning. Especially in reading the Qur'an, Allah has set rules in reading the Qur'an such as laws and rules. This study aims to describe the problems experienced by students in reading the texts of the Qur'an and hadith. This study uses a qualitative approach with descriptive-analytical methods and data collection techniques are observations. The subjects of this study were grade 3 students of MI Walisongo Semarang, totaling 45 people consisting of 6 men and 39 women. The results of the study explain the problem of reading the Qur'anic text and hadith, including: pronunciation of the sounds of the letters hijaiyah (makhorijul letters), short length of charity, and the law of reading (tajwid). And in terms of the environment, namely: students lack focus on learning materials, teacher teaching skills, lack of interest and activities of students in learning to read the Qur’an and hadith, lack of time, facilities and infrastructure for student learning, both at school and at home, and not supporting the community environment.